Fluctuation conductivity due to the preformed local pairs - Domański, T.; Barańska, M.; Solovjov, A.L. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
We investigated the properties of a system where the itinerant electrons coexist and interact with the preformed local pairs. Using the nonperturbative continuous unitary transformation technique we show that Andreev-type scattering between these charge carriers gives rise to the enhanced diamagnetic response and is accompanied by appearance of the Drude peak inside the pseudogap regime ω ≤ 2Δpg. Both effects are caused by the short-range superconducting correlations above the transition temperature Tc. In fact, the residual diamagnetism has been detected by the torque magnetometry in the lanthanum and bismuth cuprate superconductors at temperatures up to ~ 1.5Tc. In this work we show how the superconducting correlations can be observed in the ac and dc conductivity.